ANALISIS PENGARUH BRAND AWARENESS DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN (Studi pada konsumen Smartphone Oppo di Alibaba Cell Malang) - Novita Kensiwi; N. Rachma; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to analyze the effect of brand awareness and perceived quality simultaneously on purchasing decisions, analyze the effect of brand awareness on purchasing decisions, analyze the effect of perceived quality on purchasing decisions. The data collection method used a questionnaire with a sample size of 75 respondents who were taken using purposive sampling technique. Data analysis uses validity test, reliability test, normality test, classic assumption test (multicollinearity test and heteroscedasticity test, multiple linear regression and hypothesis test (F test and t test). The results showed that: brand awareness and perceived quality had a significant effect simultaneously on purchasing decisions, brand awareness had a significant effect on purchasing decisions, perceived quality had a significant effect on purchasing decisions.   Keywords: brand awareness, perceived quality, purchasing decisions